2018
DOI: 10.1038/s41598-018-29438-y
|View full text |Cite
|
Sign up to set email alerts
|

Defining the frequency of human papillomavirus and polyomavirus infection in urothelial bladder tumours

Abstract: Given the contradictory nature of the literature regarding the role of human papillomaviruses and polyomaviruses in the pathogenesis of urothelial bladder cancer (UBC), we sought to investigate the frequency of their involvement in a large cohort of primary UBCs. DNA was extracted from 689 fresh-frozen UBC tissues and screened for the presence of high-risk human papillomavirus (HPV) types 16 and 18 and BKV/JCV genomic DNA by qPCR. In positive cases, viral identity was confirmed by Sanger sequencing and viral g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 18 publications
0
46
2
Order By: Relevance
“…In nonimmunocompromised patients, JCV DNA sequences have been detected in several human malignancies, including brain, colon, prostate, esophageal, and urothelial bladder tumors …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In nonimmunocompromised patients, JCV DNA sequences have been detected in several human malignancies, including brain, colon, prostate, esophageal, and urothelial bladder tumors …”
Section: Discussionmentioning
confidence: 99%
“…In nonimmunocompromised patients, JCV DNA sequences have been detected in several human malignancies, including brain, colon, prostate, esophageal, 13 and urothelial bladder tumors. 14 In addition, as JCV persists in the kidney and urinary tract after the initial infection, 1 urinary tract cells are at risk for the oncogenic effects of this virus.…”
Section: Ki67 Vp1mentioning
confidence: 99%
“…Other malignancies associated with HPV include SCC of the skin/nose tip and skin appendages [58][59][60][61][62]. Association between HPV and bladder cancer even though without uniform conclusions has also been reported in several studies [63][64][65][66][67][68][69].…”
Section: Hpv-associated Diseases In Menmentioning
confidence: 93%
“…Other BKV pro-oncogenic mechanisms are also proposed and include induction of telomerase activity, deregulation of multiple crucial signalling pathways for proliferation (phosphoinositide-3 kinase-Akt/ protein kinase B, Wnt, and Ras/Raf/mitogen-activated kinase signalling pathways, STAT3, Notch, and hepatocyte growth factor receptor signalling pathway), and finally, induction vascular endothelial growth factor expression [98,[102][103][104][105] The majority of reports regarding association of urothelial cancer (both bladder and upper urinary tract) and BKV infection are case reports of immunocompromised patients [106][107][108][109]. It has to be emphasised that almost all of the described tumours are highgrade, highly aggressive with morphological features resembling the bladder cancers of SV40 transgenic mice (developed by the pathway of p53 and pRb inactivation) [98,110,111]. In a recent populationbased study on 55 697 transplant recipients, the risk of bladder tumours was found to be 1.7-fold higher in patients treated for presumed BKV nephropathy compared with transplant recipients without prior BKV infection [112].…”
Section: Treatmentmentioning
confidence: 99%